FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN LABA BERSIH PADA PERUSAHAAN PROPERTI - Yehezkiel Handranata; Herman Ruslim (Fakultas Ekonomi Universitas Tarumanagara, 2022)
The purpose of this empirical research is to obtain empirical evidence about the influence of a number of the audit committees, a number of the independent commissioners, institutional ownership, managerial ownership, capital structure, and firm characteristic on the growth of net profit on property companies listed on Indonesia’s Stock Exchange from 2015 to 2019. This research uses property company data that were selected using the purposive sampling method which produces 145 data. The data used in this research are secondary data in the form of financial statements. The results of this research show that number of the audit committee, a number of the independent commissioners, institutional ownership, managerial ownership, and capital structure have no significant effect on the growth of net profit, while firm characteristic has a positive effect on the growth of net profit.